Andra-Heutogogy: A new approach for teacher training - Preece, Abdul Shakour Duncan; Hamed, Popoola Kareem (Academia Industry Network, 2019)
The research evaluated a new teacher training approach called Andra-heutagogy. Andra-heutagogy combines blended learning with team teaching to enhance pre-service teachers' teaching strategies and use of IT. The researchers conducted a mixed-method study using a quasi experimental design with two groups of pre-service teachers studying at a department of education in Kuala Lumpur. The experimental group was exposed to the new Andra-heutagogical approach, while the control group experienced conventional instructional methods. Qualitative data was collected by means of classroom observation and semi-structured interviews for six participants from the experimental group. The findings revealed that participants found the approach to be an engaging and beneficial one due to their experiences of team-teaching under the guidance of an expert instructor. Andra-heutogogy therefore showed itself to be a useful new approach for teacher training that can meet the needs of 21st century teaching and learning.